Students’ Preference of Theoretical and Practical Teaching in ELT Libyan Higher Education Setting: An Action Research Study on the Impact of Integrating Technology to Language Teaching - Suweekar , Najla Ali Hamad (Scientific Journal of University of Benghazi, 2024)
Shifting the focus from merely theoretical teaching to balancing between theory and practicum in English Language Teaching (ELT) in Libyan Higher Education setting is a challenge, and it is the concern of this article. ELT Libyan students need to be capable enough to implement what they learn in universities and to integrate technology in language classrooms. At the Department of English Language in the University of Benghazi Al. Marj Campus, the author –a teacher and educator- investigated 47 eighth semester students to know their feedback about the style of instruction they are experiencing and what they prefer instead, their opinions about the practical and technological classes of the subject Technology and Language Learning E506 (taught by the author), and to assess their immediate performance after attending a workshop. Unlike their educational experience which relies on providing only theoretical knowledge, students expressed a desire to equate theoretical and practical education. They enjoyed participating in workshops as well as using technology in teaching and learning. Students performances were evident to be better, therefore, the current study recommends that attending workshops helps students teachers to revise and apply what they are learning to improve their teaching and technical skills.